Quantification of fine root responses to selenium toxicity - Hartikainen, Helinä; Pietola, Liisa; Simojoki, Asko; Xue, Tailin; Helsingin yliopisto; Michigan State University; Institute of Geography, Chinese Academy of Sciences (Agricultural and Food Science in Finland, 2001)
Research Note
Keywords: seleeni; salaatit; morfologia; raiheinät; scanning; image analysis; lettuces; morphology; Lolium; selenium; toxicity